Curricular Decoupling of Social Protection: A Pragmatic Evaluation of the Integration of Risk Management, Social Security, and Insurance in Nepal’s Secondary Education - Ghimire, Shurendra (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study examines the extent of curricular decoupling of Risk Management, Social Security, and Insurance (RMSSI) in Nepal’s secondary school education (Grades 6–12), focusing on the alignment between constitutional and policy mandates and the formal written curriculum.Design/methodology/approach: The study employs a qualitative deductive content analysis of national policy documents and school-level curricula, comparing the intended and written curriculum through the analytical lenses of curriculum alignment theory and risk society scholarship.Findings: The findings reveal a substantial disconnect between national policy intentions and curricular implementation. While policy frameworks position RMSSI as central to economic resilience and collective security, the written curriculum remains fragmented, disaster-centric, and ideologically oriented toward an allowance-driven dependency model, leaving students risk-aware but financially and institutionally unprepared.Conclusion: This curricular misalignment undermines Nepal’s transition toward a sustainable, contributory social protection system and contributes to the reproduction of formally educated yet structurally vulnerable citizens.Implications: The study highlights the need for curriculum reform that integrates RMSSI as a core life skill across compulsory subjects, aligning educational content with constitutional commitments to a socialism-oriented democracy.Originality/value: This study offers one of the first systematic, theory-driven evaluations of RMSSI integration in Nepal’s school curriculum, providing a novel framework for aligning education with social protection systems in emerging welfare states.JEL Classification: I28, I38, H52, H53, 015